2016
DOI: 10.1155/2016/1473801
|View full text |Cite
|
Sign up to set email alerts
|

Steamed and Fermented Ethanolic Extract from Codonopsis lanceolata Attenuates Amyloid‐β‐Induced Memory Impairment in Mice

Abstract: Codonopsis lanceolata (C. lanceolata) is a traditional medicinal plant used for the treatment of certain inflammatory diseases such as asthma, tonsillitis, and pharyngitis. We evaluated whether steamed and fermented C. lanceolata (SFC) extract improves amyloid-β- (Aβ-) induced learning and memory impairment in mice. The Morris water maze and passive avoidance tests were used to evaluate the effect of SFC extract. Moreover, we investigated acetylcholinesterase (AChE) activity and brain-derived neurotrophic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…These results suggest that EEFE-mediated memory and cognitive impairment may be associated with activation of the CREB/BDNF signaling. Actually, many studies have reported that CREB/BDNF activation in the brain of experimental mice facilitates successful memory retrieval (Weon et al, 2016;Wang et al, 2018;Ma et al, 2019), implying that enhancers of CREB/BDNF pathway may have the potential for treatment of AD. In this respect, EEFE may be considered one of these candidate drugs.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that EEFE-mediated memory and cognitive impairment may be associated with activation of the CREB/BDNF signaling. Actually, many studies have reported that CREB/BDNF activation in the brain of experimental mice facilitates successful memory retrieval (Weon et al, 2016;Wang et al, 2018;Ma et al, 2019), implying that enhancers of CREB/BDNF pathway may have the potential for treatment of AD. In this respect, EEFE may be considered one of these candidate drugs.…”
Section: Discussionmentioning
confidence: 99%
“…That fermentation of Codonopsis plays a role of improving memory impairment, neuroprotective and antitumour have been investigated and reported (Lee et al 2015;Weon et al 2014Weon et al , 2016. However, most of the existing reports are about Codonopsis lanceolata, and there is no precedent for C. pilosula fermented by G. sessile.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that EEFE treatment enhanced memory and cognitive function through activation of CREB/BDNF signaling. Actually, many studies have reported that CREB/BDNF activation in the brain of experimental mice facilitates successful memory retrieval [35,39,40], implying that enhancers of CREB/BDNF pathway may have the potential for treatment of AD. In this respect, EEFE may be considered one of these candidate drugs.…”
Section: Discussionmentioning
confidence: 99%